Dextromethorphan for the treatment of agitation in dementia: A pilot study: Human/Human trials: Other behavioral symptoms. (7th December 2020) - Hwang, Tzung‐Jeng; Chen, Jiahn‐Jyh; Lin, Yi‐Ting; Chan, Hung‐Yu
Abstract: Background: Agitation is highly prevalent in patients with dementia and off‐label use of antipsychotic agents for agitation is common. But antipsychotic agents are clearly associated with increased adverse effects. A recent study found dextromethorphan (DXM) and low dose quinidine may be effective for the management of agitation in patients with Alzheimer disease (AD). Methods: This is an open‐label, 10‐week study. Eligible dementia patients (AD or VaD) were enrolled. These patients received DXM 60 mg/day from Day 1 through Day 7. If the symptoms of agitation were not reduced, the dose might be gradually increased to 240 mg/day. The primary endpoint was score change in agitation domain of the Neuropsychiatric Inventory (NPI), and secondary endpoints include change on NPI total score and subscores, CGI, and MMSE. Results: A total of 16 patients were recruited. The mean (SD) of age was 79.3 (9.9) years, with male to female ratio 1:1. The mean (SD) of MMSE was 9.7 (9.7). At baseline, CGI‐Severity for agitation was 4 to 6 (mean=4.9), The mean and SD of behavioral disturbances were: 8.4 (3.5) for NPI agitation score, 8.1 (4.3) for NPI irritability score, 7.6 (4.8) for NPI aberrant motor behavior, and 58.8 (33.7) for NPI total score. At the endpoint, the mean dose of DXM was 150 mg/day. There was a significant decrease of the score of behavioral disturbance: 3.8 (3.0) for NPI agitation score (p<0.001), 4.2 (3.9) for NPI irritability score (p<0.001), 2.3 (3.9) for NPI aberrant motor behavior (p<0.036), and 24.4 (19.6) for NPI total score (p<0.001). The CGI‐I on agitation revealed 69% (n=11) with much/very much improved, 25% (n=4) minimal improved, and 6% (n=1) minimally worse. There were some mild to moderate adverse effects reported, including malaise, anemia, drowsiness, skin itching, and increased appetite. No severe adverse effects were found. Conclusions: The results of this preliminary study suggest DXM 60‐240 mg/day seem quite efficacious for the treatment of agitation in dementia and without severe adverse reactions. It may be suitable for short‐term use for control of agitation in elderly dementia patients.